AUDITOR PERFORMANCE IS REVIEWED FROM INTEGRITY, INDEPENDENCE, PROFESSIONALISM AND COMPETENCE - Jajang Prihono; Istiatin .; Sudarwati . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
This study aims to determine the effect of integrity, independence, professionalism and competence on the performance of auditors at the Klaten Regency Inspectorate Office. This study uses a quantitative descriptive approach. The population in all employees who work at the Klaten Regency Inspectorate Office is 54 people. The number of samples taken as many as 54 people or respondents. The data analysis technique used is Partial Least Square (PLS) analysis. The results showed that the influence of integrity, independence, professionalism and competence had a positive and significant effect on the performance of auditors at the Klaten Regency Inspectorate Office. It is hoped that the Klaten Regency Inspectorate Office in the future will maintain and improve the existing integrity, independence, professionalism and competence, so that the auditor's performance will also increase and be better than before.